DEVELOPMENT AND PSYCHOMETRIC PROPERTIES OF ADDICTION RECOVERY SCALE - Sulaiman, Wan Shahrazad Wan (International Journal of Psychosocial Rehabilitation, 2020)
Addiction recovery is the process of change in which individuals improve their health and well- being, yet it is difficult to find an instrument to measure this recovery process. Thus, this study was aimed to develop the Addiction Recovery Scale and evaluate its’ psychometric properties. The instrument was developed to measure four dimensions of addiction recovery with 137 respondents participated in the study. Reliability and validity of the instrument were tested using Cronbach alpha and factor analysis. Results of principal component analysis extracted four factors with acceptable eigen values and the percentage of variance explained for all factors was 41.4%. All the factors have good factor loadings between .333 to .807. Reliability analysis also showed satisfactory Cronbach alpha for all four dimensions from .809 to .978. The development of this instrument has shown the importance of the dimensions of religiosity and belief, stability and security, health, and emotional stability in addiction recovery. Through the use of this instrument, it enables agencies related with drug treatment and rehabilitation programmes to monitor the recovery of individuals involved in drug addiction